Development of a Water Quality Assessment Index for the Chania River, Kenya - Kasyoka, Robert; Onyari, Charles N.; Mbaka, James G. (Taylor and Francis, 2020)
Human-related activities are known to have deleterious effects on the water quality of aquatic ecosystems, but there is limited information on the impact of these on rivers in tropical regions, such as the Chania River in Kenya. The Chania River is an important source of water for humans and animals and provides habitat for a variety of flora and fauna. This study used a Water Quality Index (WQI) to assess the suitability of the water for human use based on selected physico-chemical parameters (nitrates, Total Dissolved solids (TDS), potassium, sulphates, chlorides, copper, manganese, pH and phosphates). Sample collection was done between October 2018 and February 2019 over the dry and the wet seasons. Generally, the WQI indicated that water quality was fair to good in the dry season (19.67 to 30.10) but fair to poor in the wet season (23.17 to 89.15). It is recommended that the riparian zone of the Chania River be protected from anthropogenic disturbances in the County Kiambu.
Keywords: human activities; impacts; riparian zone; Thika town; Water Quality Index